The Effectiveness of the Geographical Inquiry Learning Model on the Cognitive Skills of Geography Education Students in the Context of Contemporary Environmental Issues - Hariyadi, Eko; Dwi Astuti, Alfiani; Juwirda, Juwirda; Ilmadana MGB, A. (STKIP Taman Siswa Bima, 2025)
Geographical inquiry is a pedagogical model that promotes active student engagement in the development of higher-order thinking skills. Through this approach, students are encouraged to participate in a series of activities including information gathering, investigation, data analysis, and the implementation of concrete actions, enabling them to formulate effective solutions to various environmental issues. The purpose of this study is to determine the effectiveness of implementing the geographical inquiry learning model on the cognitive skills of Geography Education students at FKIP USN Kolaka. The research method used a pre-experimental research design: a non-equivalent group design with posttest only. The research subjects were students of the Geography Education Study Program, FKIP USN Kolaka, in the 2024/2025 academic year, divided into two classes, namely the control class and experimental class. Data on students’ cognitive skills were obtained using cognitive domain test questions through a posttest. Data analysis techniques were performed using descriptive statistics and independet sample t-test. The analysis results show that the average score in the experimental class had higher learning outcomes, while the t-test analysis shows that the sig value (2-tailed) of 0.000 with a t-count of 6.43 is greater than t-tabel value of 2.042, the results of the test show that geographical inquiry learning has an influence on the cognitive skills of geography education students in the context of contemporary environmental issues and is significantly effective in improving the cognitif skills of students in the Geography Education Study Program at FKIP USN Kolaka.